Genetic variability of root peel thickness and its influence in extractacle starch from cassava (manihot esculenta Crantz) roots - Pérez, J.C.; Lenis Calderon, Jorge Iván; Calle, F.; Morante, N; Sánchez, T.; Debouck, Daniel G.; Ceballos, H. (Wiley, 2011)
Cassava roots are the most important commercial product from this crop. Roots have two major components: the starchy parenchyma and the peel with higher amount of fibre and cyanogenic glucosides. In this study, a sample of 64 clones grown in replicated trials in five locations were evaluated for peel thickness (PT) that ranged from 1.48 to 2.55 mm. Roots from a sample of 33 of these clones were further analysed for the amount of extractable starch. Broad sense heritability for PT was high (0.93) compared with that for yield (0.63). The values obtained demonstrate that there is a very strong genetic component in the expression of PT. Extractable starch depended heavily on dry matter content but also on PT. In an additional evaluation, 1448 accessions from the germplasm collection were evaluated for PT and showed a wide range of variation (from 0.79 to 5.14 mm).